Evaluation of soybean genotypes against collar rot disease caused by Sclerotium rolfsii Sacc.: Evaluation of soybean genotypes against collar rot disease caused by Sclerotium rolfsii Sacc. - RAJKUMAR RAMTEKE; SURBHI DALAL; LAXMAN S RAJPUT; VENNAMPALLY NATARAJ; SHIVAKUMAR MARANNA (Journal of Oilseeds Research, 2023)
Collar rot caused by S. rolfsii is one of the economical diseases of soybean that can cause up to 30-40% yield loss in India. A total of 18 soybean genotypes were screened artificially during 2021 at ICAR-IISR, Indore, to study the virulence among the fungal isolates as well as to identify the resistance sources. Based on pathogenicity, Indore isolate (SRI) was found to be more virulent than Assam isolate (SRA). On the basis of percent emergence (PE) and the disease indices - root weight of inoculation (RWI) and ratio of root weight (RRW), genotypes JS 335, JS 20-34 and MACS 1620 were resistant against SRI whereas RSC 10-52 and JS 335 were found to be potential donors for resistance against SRA.